Reagan's "boys" and the children of the greatest generation - Bullinger, Jonathan M., 1978- author.
1 online resource.
Keywords: "During the 1980s and 1990s, aging Baby Boomer parents constructed a particular type of memory as they attempted to laud their own parents' wartime accomplishments with the label 'The Greatest Generation.' This book is the first to tell the entire story of this particular type of U.S. World War II memory begun by U.S. President Ronald Reagan in 1984, and promoted the same year by newscaster Tom Brokaw. The story continues in 1994, when it was given academic credence by historian Stephen E. Ambrose, a sensory realism and ideal American character by director Steven Spielberg and actor Tom Hanks, sloganized by Tom Brokaw in 1998, and later interpreted in light of 9/11 and new wars"--